2024
DOI: 10.1037/sgd0000607
|View full text |Cite
|
Sign up to set email alerts
|

“The default is just going to be getting misgendered”: Minority stress experiences among nonbinary adults.

Abstract: Nonbinary people make up approximately one third of the broader trans community, yet most research on trans populations focuses on the experiences of binary trans people (i.e., trans men and trans women). Research has begun to indicate that mental health disparities may differ between binary and nonbinary trans populations and that nonbinary people may be at even greater risk for some mental health disparities compared to binary trans populations. Minority stress theory provides a framework for understanding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 46 publications
(72 reference statements)
8
42
0
Order By: Relevance
“…Nevertheless, we found that youth AFAB who have nonbinary identities reported higher anxiety symptoms than youth AFAB who are transmasculine in multivariate analyses accounting for GM stressors, so it is possible that a psychosocial process outside of GM stressors is related to heightened anxiety symptoms among nonbinary youth AFAB. These disparities could be related to nonbinary-specific forms of minority stress, such as lower cultural visibility and the structural invalidation of nonbinary identities (Matsuno et al, 2022). More research is needed to determine the mechanisms of these disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we found that youth AFAB who have nonbinary identities reported higher anxiety symptoms than youth AFAB who are transmasculine in multivariate analyses accounting for GM stressors, so it is possible that a psychosocial process outside of GM stressors is related to heightened anxiety symptoms among nonbinary youth AFAB. These disparities could be related to nonbinary-specific forms of minority stress, such as lower cultural visibility and the structural invalidation of nonbinary identities (Matsuno et al, 2022). More research is needed to determine the mechanisms of these disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the authors' experiences as TGD people at sea includes forms of harm from scientists and crew members. Misgendering, both intentional and accidental, is a frequent occurrence and has documented negative effects on mental health and wellbeing (Matsuno et al., 2022; McLemore, 2018). Intentional misgendering is a form of sexual harassment (Sexual Orientation and Gender Identity (SOGI) Discrimination | U.S.…”
Section: Common Challenges Of Tgd People At Seamentioning
confidence: 99%
“…Unfortunately, the authors' experiences as TGD people at sea includes forms of harm from scientists as well as crew members. Misgendering, both manuscript submitted to AGU Advances intentional and accidental, is a frequent occurrence and has documented negative effects on mental health and wellbeing (Matsuno et al, 2022;McLemore, 2018). Intentional misgendering is a form of sexual harassment (Sexual Orientation and Gender Identity (SOGI) Discrimination | U.…”
Section: Life At Seamentioning
confidence: 99%